Performance of the EOMIP-CCSD(2) method for determining the structure and properties of doublet radicals: a benchmark investigation - Dutta, Achintya Kumar; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2013)
We present a benchmark study on the performance of the EOMIP-CCSD(2) method for computation of structure and properties of doublet radicals. The EOMIP-CCSD(2) method is a second-order approximation to the standard EOMIP-CCSD method. By retaining the black box nature of the standard EOMIP-CCSD method and adding favorable N-5 scaling, the EOMIP-CCSD(2) method can become the method of choice for predicting the structure and spectroscopic properties of large doublet radicals. The EOMIP-CCSD(2) method overcomes the typical problems associated with the standard single reference ab initio treatment of doublet radicals. We compare our results for geometries and harmonic vibrational frequencies with those obtained using the standard EOMIP-CCSD method, as well as unrestricted Hartree-Fock (UHF)- and restricted open-shell Hartree-Fock (ROHF)-based single-reference coupled-cluster and second order many-body perturbation theory (MBPT(2)) methods. The effect of the basis set on the quality of the results has been studied using a hierarchy of Dunning's correlation-consistent aug-cc-pVXZ (X = D, T, Q) basis sets. Numerical results show that the EOMIP-CCSD(2) method, despite its N-5 scaling, gives better agreement with experimental results, compared to the UHF- and ROHF-based MBPT(2), as well as the single-reference coupled-cluster methods.

Polarizability of few electron quantum dots: extended coupled-cluster response approach - Heidari, Ideh; Vaval, Nayana; Pal, Sourav; Kanhere, Dilip G. (Chemical Physics Letters, 2013)
The dipole polarizability is studied for few electron quantum dots using extended coupled cluster linear response method (ECCLR). The polarizability of pure parabolic quantum dots depends only on the number of electrons and the parabolic confinement strength. We added impurity in a GAUSSIAN form to the external parabolic potential and used ECCLR to calculate polarizability. To examine the effect of external potential, we changed the parabolic confinement to square-well and repeated all calculations. We mainly looked at eigenvalue spectrum and charge density specially when the system shifts towards lower density regions. (C) 2012 Elsevier B. V. All rights reserved.

Partitioned EOMEA-MBPT(2): an efficient N-5 scaling method for calculation of electron affinities - Dutta, Achintya Kumar; Gupta, Jitendra; Pathak, Himadri; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2014)
We present an N-5 scaling modification to the standard EOMEA-CCSD method, based on the matrix partitioning technique and perturbative approximations. The method has lower computational scaling and smaller storage requirements than the standard EOMEA-CCSD method and, therefore, can be used to calculate electron affinities of large molecules and clusters. The performance and capabilities of the new method have been benchmarked with the standard EOMEA-CCSD method, for a test set of 20 small molecules, and the average absolute deviation is only 0.03 eV. The method is further used to investigate electron affinities of DNA and RNA nucleobases, and the results are in excellent agreement with the experimental values.

Partial triples excitation to the fock space multi-reference singles and doubles: dipole moment of doublet radicals - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (Proceedings of the International Conference of Computational Methods in Sciences and Engineering 2010 (ICCMSE-2010), 2015)
We present the partial triples effect on the dipole moment of doublet radicals in Lagrangian formulation of Fockspace multi-reference coupled cluster response method(A FSMRCC). This specific scheme uses non-iterative triples, in addition to singles and doubles excitations(A FSMRCCSD(T*)), which accounts for the effects appearing at least at the third order in dipole moment. This method is applied to the ground states of small radicals.
Keywords: Dipole moment; Multi-reference; Triples